Indigenous Technologies and their Applicability in Classroom Instructions in Secondary Level - Bhattarai, Taranath (Butwal Campus Journal, 2024)
Indigenous technologies as local resources reflect definite practical skills that can be applied in classroom in order to bring real life tasks and activities for the students. This study aims at identifying the locally available indigenous technologies in school level classroom instructions and analyzes the applicability of such technologies in classroom instructions for the development of activity-oriented practical education. Based on qualitative method, the data have been collected through PRA, observation, and semi- structured interview. The collected data have been analyzed by carrying out immersion, understanding, abstraction, synthesis, illumination of phenomena and integration and critique of findings. The key finding of this study shows abundances of locally available technologies that can be applied in classroom instructions and can be implemented for the development of task-based, practical classroom instructions in study area and in general.